Evaluation of Foveal and Parafoveal Microvascular Changes Using Optical Coherence Tomography Angiography in Type 2 Diabetes Patients without Clinical Diabetic Retinopathy in South Korea - Young Gun Park; Minhee Kim; Young Jung Roh (Journal of Diabetes Research)
The aim of this study was to investigate foveal and parafoveal microvascular changes in retinal vascular plexuses in patients with type 2 diabetes mellitus (DM) without clinical diabetic retinopathy (NDR) using optical coherence tomography angiography (OCTA) in South Korea. We included 64 patients in the NDR group and included 48 healthy control subjects for comparison. All subjects underwent ocular examination with visual acuity and wide-field fundus photos. Foveal and parafoveal vessel density and foveal avascular zone (FAZ) area (mm2) in the superficial capillary plexus (SCP) and deep capillary plexus (DCP) were analyzed. Foveal vessel densities in both the SCP and DCP were decreased in the NDR group compared to the controls (p=0.034 and 0.001, respectively). Vessel densities in the superior and inferior parafoveae in the DCP were decreased in the NDR group compared to the controls (p=0.006 and 0.034, respectively). The FAZs of the SCP and DCP were significantly different between the NDR group and the controls (p=0.003 and 0.001, respectively). The average vessel densities of the SCP and DCP were not correlated with HbA1c, serum creatinine, or the duration of DM in the NDR group. We demonstrated that OCTA can identify early-stage DR before the manifestation of clinically apparent retinopathy in diabetic eyes. Diabetic patients without clinical DR have microvascular alterations (foveal vessel density, parts of the parafovea, and enlarged FAZ) in the SCP and DCP. Our results suggest that OCTA might be a promising tool for early detection of eyes with DR.